Students’ social entrepreneurship knowledge, skills and attitude, as correlate of innovative social enterprise in University of Ibadan, Nigeria (2020)
The high prevalence of youth unemployment has resulted in a monumental loss in building a great nation. This necessitated the introduction of social entrepreneurship in the University to prepare youth for the future. However, there is little or no report on youth preparedness to take up social enterprising after their exposure to the course. This study, therefore, assessed the students’ social entrepreneurship knowledge, skills, and attitude as correlates with the creation of innovative social enterprise in Ibadan. Four hypotheses were formulated and tested at 0.05 level of significance. The study adopted an ex-post facto design. Fifty (50) Masters students that offered social entrepreneurship course in the Centre for Entrepreneurship and Innovation in the 2018/2019 session were purposively selected for the study. SKT - (r= 0.82), SATO (r= 0.76) and SSS (r=0.78) were used to collect data and analysed using, Pearson Product Moment Correlation. The study revealed that there is a low positive correlation between students’ social entrepreneurship knowledge and students’ creation of innovative social enterprises (r = 0.010; P<0.05); there is a high positive relationship between students’ entrepreneurship skills and creation of innovative social, enterprises (r = 0.936; P<0.05) and high positive correlation between students' entrepreneurship attitudes and creation of innovative Social Enterprises (r = 0.912; P < 0.05). It can be concluded from this study that students’ social entrepreneurship knowledge, attitudes, and skills are key ingredients to promote social enterprise to be self-reliant while developing their communities. Social entrepreneurship should, therefore, be integrated into the University curriculum, to encourage students to think of solutions to challenges facing society while bringing up social innovators and gainfully employment.